Constituyentes químicos y actividad antiinflamatoriade Marcetia taxifolia - Baptista, Jani; Chávez, Katiuska; Torrico, Fátima; Trejo, Ernesto; Garcia, Carmen; Urbina, Jensaida; Carrasco, José; Taddei, Antonieta; Tillett, Stephen; Suárez, Alírica (Ciencia, 2016)
Ver Resumen PDF.